Effect of Fusarium graminearum and F. poae infection on Barley and Malt Quality - Schwarz, Paul B.; Schwarz, Jurgen G.; Zhou, Alice; Prom, Louis K.; Steffenson, Brian J. (BrewingScience, 2001)
Objectives of this research were to investigate barley and malt quality as impacted by Fusarium graminearum and F. poae infection. F. graminearum is the primary pathogen responsible for the recent Fusarium Head Blight epidemics in the upper Midwestern USA, while F. poae is involved to a lesser extent. Inoculation and seed production in the greenhouse were utilized as a means of reducing the interfering effects of other microflora. Harvested seed from control and infected plants was micro-malted, and the malt quality of control and inoculated samples analyzed. Large amounts of deoxynivalenol,15-acetyl deoxynivalenol and zearalenone were present on samples inoculated with F. graminearum, while only small amounts of nivalenol were detected on the F. poae infected samples. The most noticeable effects of infection on barley quality were reduction in kernel plumpness and germination. In general the effects of F. graminearum on both barley and malt quality were more pronounced than those of F. poae. Reduction in kernel plumpness somewhat confounds the interpretation of malt quality results. However, infection with Fusarium did appear to have very pronounced effects on increasing wort soluble nitrogen, free amino nitrogen and wort color. These observations suggested increased proteolysis in the infected material. This is particularly true if one considers that up to 40% of kernels in the infected samples did not germinate, and would thus be expected to display reduced protease activity.